(untitled) (Ius Novum, 2026)
The paper analyses the form and place of human will in the foundations of criminal liability. It explains the necessity of will for the traditional criminal liability of natural persons and presents a comparison with the possible criminal liability of autonomous and non-autonomous systems equipped with artificial intelligence. The conclusions of the paper are negative with regard to the possible direct liability of such systems. A solution is proposed in the form of criminal liability for persons who create, control and monitor autonomous and nonautonomous systems.